THE POLYLOGARITHM HELPS TO UNDERSTAND THE RELATION BETWEEN BLACK HOLE’S ENTROPY AND AREA - Muñoz Muñoz, Francisco Ricardo (Innovaciencia, 2014)
Introduction: It begins with definitions and explanations of concepts involved in the dynamics of black holes. Materials and methods: review of the subject is developed based on the fact that the black hole is surrounded by a “sea of photons” created through the process of accretion, reaching to obtain the relationship between entropy and the area of a black hole in accordance with the scientific literature. Results and discussion: In this paper, a derivation of the relationship between entropy and area of a stationary black hole, loaded from the establishment of a radiation bath of photons corresponding to the frequency of lightning occurs X. Conclusions: In the process mathematical expressions arise shortly worked in formal physics courses at the undergraduate level, as is the polylogarithm functionJonquière or present throughout the developments that follow, once established for the first time.
Keywords: Entropy, Area, Black hole, X rays, polylogarithm.